Case reportBullous pyoderma gangrenosum associated with pancytopenia of unknown origin - Wolska, Katarzyna; Michalska-Jakubus, Małgorzata; Pucuła, Joanna; Chodorowska, Grażyna; Dzida, Grzegorz; Mosiewicz, Jerzy; Prystupa, Andrzej; Podhorecka, Monika; Krasowska, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Pyoderma gangrenosum (PG) is a neutrophilic dermatosis of unknown origin. Clinically it starts with a pustule, nodule or bulla that rapidly progresses and turns into a painful ulcer with raised, undermined borders. The etiopathogenesis of PG remains unknown. However it is frequently associated with systemic diseases such as inflammatory bowel disease (IBD), haematological disorders or arthritis. The latest multicentric retrospective analysis published by Ghazal et al. shows that anaemia has been observed very often in German patients suffering from PG (in 45.6% of 259) so this disorder is supposed to be a possible cofactor in the pathogenesis of PG. According to its progressive course, patients require intensive diagnostic procedures and rapid initiation of the treatment. In this article, we report a case of bullous pyoderma gangrenosum in association with pancytopenia of unknown origin, according to its diagnostic and therapeutic difficulties.